Microwave Assisted Synthesis and Bioactivity of s-Triazolo[3,4-b][1,3,4] Thiadiazoles, s-Triazolo [3,4-b][1,3,4] Thiadiazines and s-Triazolo [3',4':2,3]-Thiadiazino[5,6-b] Quinoxaline - Shiradkar, Mahendra; Shivaprasad, H.N. (Asian Journal of Chemistry, 2010)
The solvent free conditions using microwave irradiation, the condensation of N-[3-(4-amino-5-mercapto-4H [1,2,4] triazol-3-yl)-4,5-dimethyl-thiophene-2-yl]-acetamide (I) with chloroacetic acid, -haloketone and benzoin furnished condensed products [1,2,4] triazolo [3,4-b] [1,3,4] thiadiazine derivative, viz., II, III, IV respectively. Similarly, the condensation with 2,3-dichloro quinoxaline, carbon disulphide, aromatic carboxylic acid and aromatic carboxaldehydes furnished the cyclic products [1,2,4] triazolo [3,4-b] [1,3,4] thiadiazole derivatives, viz., V, VI, VII, VIII respectively. The compounds have been charactetrized on the basis of elemental analysis and spectral data. The antibacterial, antifungal and antitubercular activities of the compounds have also been evaluated.